2017
DOI: 10.1007/978-4-431-56550-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Drebrin in Synaptic Plasticity

Abstract: Synaptic plasticity underlies higher brain function such as learning and memory, and the actin cytoskeleton in dendritic spines composing excitatory postsynaptic sites plays a pivotal role in synaptic plasticity. In this chapter, we review the role of drebrin in the regulation of the actin cytoskeleton during synaptic plasticity, under long-term potentiation (LTP) and long-term depression (LTD). Dendritic spines have two F-actin pools, drebrin-decorated stable F-actin (DF-actin) and drebrin-free dynamic F-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…These three elements (neurofilaments, microfilaments, and microtubules) work together to guarantee a proper formation of the nervous system during the embryonic development and to assure its function in adulthood. There are three particular events where the function of cytoskeletal proteins is required: first, during embryonic development, where the cytoskeleton participates in the growth and guidance of axons (for a review see, [13,14]); second, during adult life, where neurons depend on the cytoskeleton for maintaining neuronal homeostasis and neuronal plasticity [15][16][17][18]; and third, when the peripheral axon needs to regenerate after being injured. In this last event, peripheral neurons (for a review, see [19]) require a specific set of cytoskeletal proteins to ensure nerve regeneration upon damage [20,21].…”
Section: Neuronal Cytoskeletonmentioning
confidence: 99%
“…These three elements (neurofilaments, microfilaments, and microtubules) work together to guarantee a proper formation of the nervous system during the embryonic development and to assure its function in adulthood. There are three particular events where the function of cytoskeletal proteins is required: first, during embryonic development, where the cytoskeleton participates in the growth and guidance of axons (for a review see, [13,14]); second, during adult life, where neurons depend on the cytoskeleton for maintaining neuronal homeostasis and neuronal plasticity [15][16][17][18]; and third, when the peripheral axon needs to regenerate after being injured. In this last event, peripheral neurons (for a review, see [19]) require a specific set of cytoskeletal proteins to ensure nerve regeneration upon damage [20,21].…”
Section: Neuronal Cytoskeletonmentioning
confidence: 99%
“…As previously mentioned, drebrin exodus occurs during the initial stage of synaptic plasticity, such as LTP and LTD. However, during LTP stimulation, the drebrin exodus is transient (Sekino et al., 2017). Whether these drugs induce LTP or LTD should be investigated by determining whether the drebrin exodus is transient following drug treatment, using the live‐cell imaging of GFP‐drebrin‐transfected neurons (Mizui et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Ca2+ recovery and AMPAR increase are harmonized and induce the re-accumulation of DF-actin and change the dendritic spines from the excited state to a steady state during LTP maintenance. AMPAR endocytosis is facilitated due to the inhibition of re-accumulation of DF-actin caused by a prolonged increase in intracellular Ca2+ during LTD. Because of the positive feedback loop during AMPAR decrease and drebrin re-accumulation inhibition, the dendritic spines are found to be unstable during LTD maintenance [22]. The research on the effect of sirtuin 2 (SIRT2) on synaptic plasticity and cognitive function has demonstrated that SIRT2 acts as an AMPAR deacetylation and causes protein accumulation.…”
Section: Reviewmentioning
confidence: 99%